On Representative Trust - Charles Bellemare; Sabine Kröger (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
This paper combines an economic experiment with survey data to investigate determinants of trust and trustworthiness in the Dutch society. We contrast the inferences which can be made on the trust propensity using stated and revealed measures and we test for participation bias in our experiment. We find that middle aged and educated individuals trust relatively more but are relatively less trustworthy. The effect of age and religion on trust is shown to depend heavily on whether experimental or survey trust measures are used. We find no evidence of participation bias in any experimental decisions.
urn:nbn:de:kobv:11-10050278
Keywords: Z13; C10; C90; 330; Measuring trust and trustworthiness; Experiments; Representative samples; Vertrauen; Social Capital; Experiment; Niederlande